2019
DOI: 10.3390/medicina55120776
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Biochemical Description of Brain Oxidative Stress Status in Irritable Bowel Syndrome Contention-Stress Rat Model

Abstract: Background and objectives: Oxidative stress and inflammation have been implicated in the etiology of irritable bowel syndrome (IBS), a common gastrointestinal functional disease. This study aimed to further characterize the contention-stress rat model by exploring a possible correlation between oxidative stress markers measured in brain tissues with behavioral components of the aforementioned model. Thus, it is hereby proposed a possible IBS animal model relevant to pharmacological and complementary medicine s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 28 publications
3
12
0
Order By: Relevance
“…Oxidative Medicine and Cellular Longevity important risk factor for IBS pathology [16,35]. Thus, in this study, we showed that oxidative changes occur also in tear samples of IBS patients.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Oxidative Medicine and Cellular Longevity important risk factor for IBS pathology [16,35]. Thus, in this study, we showed that oxidative changes occur also in tear samples of IBS patients.…”
Section: Discussionsupporting
confidence: 62%
“…In this way, oxidative stress was shown to be significant in both systemic and mucosal levels as a result of innate immune dysfunction in IBS pathogenesis [15]. Moreover, our group previously showed that oxidative stress could be an important component of IBS being present in the cerebral tissues in a significant correlation with the exhibited behaviour [16,17].…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Moreover, they observed that the administration of plant mixture and spasmolytic agents changed the oxidative stress imbalance in colonic cells together with antioxidant capacity improvement, but with no evidence on the correlation type between harmful events and antioxidant defense. Similar studies also reported links between smooth muscles activity and total antioxidant capacity in a wrap-restrained IBS model [72] and oxidative stress and contention-stress IBS model [108], choline precursor and intestinal oxidative signaling in acetic acid-induced IBS rat model [109], circadian rhythm hormone and systemic oxidative stress in noise-stress gastrointestinal distress rat model [73]. In this way, our recent results showed that in a contention-stress IBS model, brain oxidative stress processes are significantly correlated to behavioral parameters suggesting that strong connection between the digestive system, enteric nervous system, and the central nervous system lead to the known IBS symptoms [108].…”
Section: Oxidative Way Of Thinkingsupporting
confidence: 62%
“…Still, the common ground between some of the mentioned psychiatric illnesses (which are subtypes of affective syndromes) and, according to ROME IV criteria, IBS is the lower or greater extent of stress axis impairment [47]. Previous studies have shown that oxidative stress changes also occurred in stress-based animal models [46,48,49]. This could be a specific piece of evidence that suggests that a central nervous modulation pathway is implicated in IBS pathophysiology, with oxidative stress being a possible signaling pathway but also an unwanted effect.…”
Section: Irritable Bowel Syndrome Pathophysiology and Promoting Factorsmentioning
confidence: 99%